Negative Regulation Of T Cell Activation And Function By CIN85 Adaptor Protein - Kong, Mei Suen (2017)
Antigen recognition by T cell receptor (TCR) induces intracellular signaling cascades leading to T cell activation, subsequently inducing cellular proliferation and various effector functions. Adaptor proteins play important roles in T cell signaling by creating nodes to recruit signaling proteins and form signal complexes to regulate the direction of signaling. Casitas B-lineage lymphoma (Cbl)-interacting protein of 85 kDa (CIN85) is an adaptor protein, originally identified as a Cbl-binding protein, and was suggested to be involved in the internalization and degradation of receptors and kinases. Nevertheless, the physiological function of CIN85 in T cells is unknown.